1982
DOI: 10.1063/1.331272
|View full text |Cite
|
Sign up to set email alerts
|

Non-Newtonian viscous flow in glass

Abstract: The viscosity of a soda-lime silica glass was measured at high strain rates. The data show non-Newtonian viscous flow in this inorganic oxide glass with the viscosity values below the expected Newtonian value. Following the imposition of large, steady strain rates, the observed stress increases with time to a maximum and then decreases to a time-independent value. A comparison of the viscosity behavior of this glass with the molecular dynamics results in a ’’Lennard-Jones’’ glass shows a number of points of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
94
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 7 publications
18
94
0
1
Order By: Relevance
“…These experimental results indicate shear-thinning behavior with the viscosity decreasing with increasing strain rate while the stress continues to increase near the glass transition temperature of the material [Webb and Dingwell, 1990a;Simmons, 1998]. Such a feature of the steady-state viscosity is frequently represented by an empirical function of strain rate [Simmons et al, 1982;Simmons, 1998]. Bottinga [1994a] attributed the viscosity reduction to a change of configurational entropy due to accumulation of elastic energy in the material and represented the viscosity as a function of the elastic energy.…”
Section: Introductionmentioning
confidence: 99%
“…These experimental results indicate shear-thinning behavior with the viscosity decreasing with increasing strain rate while the stress continues to increase near the glass transition temperature of the material [Webb and Dingwell, 1990a;Simmons, 1998]. Such a feature of the steady-state viscosity is frequently represented by an empirical function of strain rate [Simmons et al, 1982;Simmons, 1998]. Bottinga [1994a] attributed the viscosity reduction to a change of configurational entropy due to accumulation of elastic energy in the material and represented the viscosity as a function of the elastic energy.…”
Section: Introductionmentioning
confidence: 99%
“…A complete understanding of magma rheology requires a comprehensive description of the rheology of the melt phase [Shaw, 1965], Most studies of shear viscosities of Silicate melts have been conducted at conditions of relatively high temperatures and low viscosities (see compilations by Bottinga and Weill [1972], Bansal and Doremus [1986], and Ryan and Blevins [1987]). In cases where the stress-strain rate relationship has been investigated over a significant ränge of strain rate, both Newtonian behavior (i.e., linear stress-strain rate relationship) [e.g., Scarfe et al, 1983] and non-Newtonian behavior [e.g., Li and Vhlmann, 1970;Simmons et al, 1982;Spera et al, 1982] have been observed. [1989] suggested that the strain rates above which non-Newtonian behavior is expected to occur in Silicate melts can be predicted from linear viscoelastic theory.…”
Section: Introductionmentioning
confidence: 99%
“…10. Similar decrease in viscosity with strain rate has been observed at high stress and high strain rate conditions in many kinds of amorphous and glassy materials such as oxide glass materials, 21,22) amorphous polymer materials, 23) metallic glass alloys, 24) while these materials usually exhibit Newtonian viscous flow at low stress and low strain rate conditions at relatively high temperatures. In case of polymer materials, such decrease in viscosity with strain rate is 23) It is however difficult for this Si-B-C-N ceramics to explain the decrease in viscosity by the entanglements of intermolecular chains, since the atomic configuration is not constituted of long molecular chains but is based on aperiodic connections of tetrahedral structure.…”
Section: Discussionmentioning
confidence: 63%